Pilot study of (89)Zr-bevacizumab positron emission tomography in patients with advanced non-small cell lung cancer - Bahce, Idris (EJNMMI Res, 2014)
BACKGROUND: The aim of this pilot study was to evaluate whether the uptake of (89)Zr-bevacizumab in non-small cell lung cancer (NSCLC) tumors could be visualized and quantified. The correlation between tumor (89)Zr-bevacizumab uptake and tumor response to antitumor therapy with a bevacizumab-based regimen was explored. METHODS: Seven NSCLC patients underwent static PET scans at days 4 and 7 after injection of 36.4 ± 0.9 MBq (mean ± SD) (89)Zr-bevacizumab, prior to commencing carboplatin-paclitaxel-bevacizumab chemotherapy (CPB). Overall survival (OS) and progression-free survival (PFS) to CPB followed by bevacizumab maintenance therapy was correlated to tumor tracer uptake, quantified using peak standardized uptake values (SUV(peak)). RESULTS: Zr-bevacizumab uptake (SUV(peak)) was approximately four times higher in tumor tissues (primary tumor and metastases) than in non-tumor tissues (healthy muscle, lung, and fat) on days 4 and 7. A positive trend but no significant correlation could be found between SUV(peak) and OS or PFS. CONCLUSIONS: This pilot study shows that (89)Zr-bevacizumab PET imaging in NSCLC is feasible. Further investigation to validate this technique as a predictive biomarker for selecting patients for bevacizumab treatment is warranted. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13550-014-0035-5) contains supplementary material, which is available to authorized users.